Energy efficiency through green in Malaysia / Mohd Zul Hafizie Mohd Khaidz - Mohd Khaidz, Mohd Zul Hafizie (2012)
This is a summary from the previous works on the energy efficiency for green and conventional design which is more on design strategies. This design strategy was developed from the overseas where it is used a high technologies on building to reduce energy used. Since there were so many promoted from the effectiveness on green building, many countries have applied the green building to reduce energy consumption in building. This study has been supported by the Ministry of Energy, Green Technology and Water, Malaysia or also known as KeTTHA and the Energy Commission Malaysia and the conventional buildings are Plaza Perangsang & Telekom Malaysia Berhad as the case study. From the study, energy efficiency’s concept is one of the elements which helping to reduce the use of electricity consumption by maximizing the use of natural daylight as well as the use of good ventilation. This concept will be explained in detail in chapter 2. Meanwhile in chapter 5 is study about design strategies on building that is divided into two types know as passive and active design. Through these design strategies, we found that both elements play an important role in building energy efficiency. Today, our country still at the introductory stage and experimental process compared to other countries that already use green technology to reduce energy consumption. That is why, this chapter is also combines with recent practice/technologies of energy efficiency that was used in green building and common design practice in our country.